Pendampingan Kesetaraan Paket-C Mata Pelajaran Matematika Semasa Pandemi Covid-19 di LPKA Batam - Himmi, Nailul; Agustyaningrum, Nina; Husna, Asmaul (Jurnal Abdimas Adpi Sosial dan Humaniora, 2021)
Education is the right of all Indonesian citizens guaranteed in Constitution of the Republic Indonesia, including children who are in criminal status. Criminal children are placed in LPKA with a maximum age of 18 years with compulsory education for 9 years. LPKA Batam provides assistance to the package C equivalence program aimed at fulfilling the learning program from the government even though it is in the status of a criminal child. LPKA is conducting moderation in the field of education, namely by online learning related to outbreak of COVID-19 since early 2020 when government implementing the PSBB policy. One of the education programs at LPKA Batam is the package C equivalency learning assistance program wich one subjects is mathematics. The problems in the learning process are the different initial abilities of students and limitations in terms of convenience and flexibility of learning while online. Thus, tutors use Google Meet for virtual meeting learning by providing material in the form of PPT or LKS. The tutor teaches understanding of mathematical concepts according to the curriculum and fosters learning motivation for the target children who take part in the package C equivalence program. At the end of the lesson, the tutor provides an evaluation of the material given as much as one question and is completed directly at the meeting. During the learning process students are very enthusiastic about receiving the material, students can solve r outine questions well, but need more assistance in solving non-routine questions. The implementation of the package C equivalence program mentoring activities in mathematics at LPKA Batam went well as seen from the responses of students who played an active role from the beginning to the end of the activity